THE PRACTICAL STATUS OF IMPLEMENTING ESG PRINCIPLES IN UZBEKISTAN (European Journal of Economics, Finance and Business Development, 2025)
The implementation of Environmental, Social, and Governance (ESG) principles in Uzbekistan is gaining prominence as the country seeks to align its economic development with sustainable practices. This article examines the current status of ESG integration in various sectors within Uzbekistan, highlighting the challenges and opportunities that arise in a transitional economy. It evaluates the regulatory frameworks, stakeholder engagement, and the role of public and private enterprises in advancing ESG initiatives. The findings underscore the necessity for a comprehensive approach that fosters collaboration between government, businesses, and civil society to promote a sustainable future in Uzbekistan.